Epidemiological profile of diseases transmitted by insect vectors in Brazilian municipalities located in the border region with Argentina (Research, Society and Development, 2021)
Vector diseases have become a permanent concern in the health field and have endemic characteristics that challenge public health. This study aimed to describe the epidemiological profile of diseases transmitted by insect vectors in Brazilian municipalities located on the border with Argentina. This is a quantitative retrospective and cross-sectional study, whose data were obtained from the Information System for Notifiable Diseases (SINAN). The diseases addressed were dengue, yellow fever, chikungunya fever, leishmaniasis and zika virus in municipalities located in the state of Rio Grande do Sul (Barra do Guarita, Derrubadas and Esperança do Sul) and in Santa Catarina (Guaraciaba, Itapiranga, Paraiso, Santa Helena and Tunápolis), for the period 2014 to 2019. Sporadic isolated cases of the diseases were observed in the municipalities. There was a higher incidence of cases in the state of Santa Catarina, with a predominance of males, whites and urban dwellers. The months with the highest notifications were March, April and May, with no hospital admissions and most progressing to cure. There is a lack of studies on the geographic distribution and dispersion of vectors, as well as the diseases transmitted by them in the border region. The results of this research contribute to the foundation of public health polices and to support specific control actions in municipalities located in this region.